Tax literacy rate among taxpayers: evidence from Malaysia - Abdul Latiff, Ahmed Razman; Amin Noordin, Bany Ariffin; Che Omar, Mohamad Raflis; Agus Harjito, Dwipraptono (SciVision, 2005)
The extent of taxpayer knowledge can have a major impact on the degree of compliance with taxation rules and regulation. Low knowledge creates uncertainty about requirements of the tax regulation and can lead to high degree of involuntary non-compliance. This study highlighted the importance of taxation knowledge by measuring Malaysian’s tax payers’ tax literacy rate taking into consideration the following criteria: 1) Individual ability to fill the tax return form independently, 2) Taxpayer’s interest in learning about tax, and 3) Incident of errors in filling the tax return forms. Questionnaires were used in this study to ascertain the tax literacy rate. The results indicate that among the respondents, professionals group has the highest percentage of tax literacy and the formers have the lowest percentage. Majority of the businessmen paid for services for filling tax return forms and high rank officers are the highest among the group for not employing others for filling the tax forms. Businessmen have the highest incidence of error in filling tax return form and most of teachers reported no error in filling such forms. Most business-men showed interests and were willing to spend time to learn about taxation. They perceived taxation knowledge as an important tool for themselves and also for their family. Overall results indicate that more than 60% of respondents are tax literate. However, a significant number of them are actually‘ functionally tax illiterate’. Most of them thought that they knew a lot about taxation as they had read them in the tax literature sent to them by the IRB. However, the evidence was contrary to this conjecture. The information on the extent of taxpayers’ knowledge is potentially useful to the tax authorities to assist them in developing effective compliance enhancement policies